2021
DOI: 10.1094/pdis-04-21-0718-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Diaporthe ueckerae Causing Stem Canker on Soybean (Glycine max) in Colombia

Abstract: In October 2018, soybean plants displaying elongated black to reddish-brown lesions on stems were observed in a field planted to the cv. BRS Serena in the locality of Puerto López (Meta, Colombia), with 20% incidence of diseased plants. Symptomatic stems were collected from five plants, and small pieces (∼5 mm2) were surface sterilized, plated on potato dextrose agar (PDA) and incubated for 2 weeks at 25°C in darkness. Three fungal isolates with similar morphology were obtained, i.e., by subculturing single hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“… Diaporthe ueckeri (syn. D. miriciae , Gao et al 2016 ) has been reported in Australia, Colombia and the USA, on Cucumis melo ( Cucurbitaceae , Cucurbitales ), Glycine max ( Fabaceae , Fabales ) and Helianthus annuus ( Asteraceae , Asterales ) ( Thompson et al 2015 ; Udayanga et al 2015 ; López-Cardona et al 2021 ). Diaporthe thunbergiicola has been only isolated from Thunbergia laurifolia ( Acanthaceae , Lamiales ) in Thailand ( Liu et al 2015 ).…”
Section: Results and Discussionmentioning
confidence: 95%
“… Diaporthe ueckeri (syn. D. miriciae , Gao et al 2016 ) has been reported in Australia, Colombia and the USA, on Cucumis melo ( Cucurbitaceae , Cucurbitales ), Glycine max ( Fabaceae , Fabales ) and Helianthus annuus ( Asteraceae , Asterales ) ( Thompson et al 2015 ; Udayanga et al 2015 ; López-Cardona et al 2021 ). Diaporthe thunbergiicola has been only isolated from Thunbergia laurifolia ( Acanthaceae , Lamiales ) in Thailand ( Liu et al 2015 ).…”
Section: Results and Discussionmentioning
confidence: 95%
“…are able to infect a range of other plants when artificially inoculated (Li et al, 2010). This is the case for D. caulivora, D. longicolla, D. gulyae, D. miriciae, D. cucurbitae and D. helianthi, which were able to cause stem canker in soybean and sunflower upon inoculation assays (Floyd & Malvick, 2022;López-Cardona et al, 2021;Mathew et al, 2018;Mena et al, 2020).…”
Section: Host Plant Speciesmentioning
confidence: 97%
“…gulyae and D . miriciae were also detected in SSC symptomatic soybean plants in North Dakota, United States, and in Meta, Colombia (López‐Cardona et al., 2021; Mathew et al., 2018). Recently, D .…”
Section: The Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Puccinia thaliae, Athelia rolfsii, Talaromyces siamensis, Neoscytalidium dimidiatum, Nigrospora sphaerica, Nigrospora aurantiaca, Colletotrichum siamense, Lasiodiplodia theobromae, Neopestalotiopsis cubana, Epicoccum sorghinum, Fusarium oxysporum, Diaporthe ueckerae, Hypoxylon hypomiltum, Fusarium proliferatum, Daldinia eschscholtzii, and Macrophomina phaseolina, and parasitic plants, viz. Cuscuta australis and Cassytha filiformis, are the common pathogens that have been reported to cause plant disease (Rattan, 2005;Li et al, 2015;Ghuffar et al, 2018;Lee et al, 2019;Elahi et al, 2021;López-Cardona et al, 2021;b;c;g;i;j;. To identify and detect the pathogens, the PCR is used to target the specific regions in pathogens' genomic DNA (Lau, Botella, 2017).…”
Section: Introductionmentioning
confidence: 99%